2014
DOI: 10.2478/jomb-2014-0011
|View full text |Cite
|
Sign up to set email alerts
|

The Phenotype Distribution of Paraoxonase-1 in Patients with Multiple Myeloma, Bladder, and Colorectal Cancer

Abstract: Background: Human serum paraoxonase-1 (PON1) shows wide variation among different ethnic groups around the world. The aim of the present study was to determine the phenotype distribution and enzymatic activity of PON1 and ARE (arylesterase) in colorectal cancer (CRC), bladder cancer (BC) and multiple myeloma (MM) patients compared to healthy subjects. Methods: A total of 160 subjects (40 CRC patients, 40 BC patients, 40 MM patients and 40 healthy controls) were admitted to the study. The phenotype distrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 22 publications
3
5
0
Order By: Relevance
“…In agreement with the present study, previous reports of Ellidag et al (2014), they determined the phenotype distribution and enzymatic activity of PON1 and ARE in CRC, bladder cancer and multiple myeloma patients as compared to healthy subjects. PON 1 and ARE activities were significantly lower in the cancer patients as compared to the control group.…”
Section: Discussionsupporting
confidence: 93%
“…In agreement with the present study, previous reports of Ellidag et al (2014), they determined the phenotype distribution and enzymatic activity of PON1 and ARE in CRC, bladder cancer and multiple myeloma patients as compared to healthy subjects. PON 1 and ARE activities were significantly lower in the cancer patients as compared to the control group.…”
Section: Discussionsupporting
confidence: 93%
“…The frequency of the PON1 R allele in the current study was in line with previous studies carried out on this population. Our previous study revealed that the frequency of the R allele in cancer patients was 0.28 [ 16 ]. Karakaya et al .…”
Section: Discussionmentioning
confidence: 99%
“…In Group II, CEA sensitivity alone was the same, the specificity of both CEA and CA 19-9 was lower and the sensitivity and specificity of the combined detection of CEA and CA 19-9 were also lower in relation to the Group I, which was the group with patients suffering from CRC in all stages of the disease ( Table II ). In addition to the widely used tumor markers CEA and CA 19-9, there is an indication of the importance of new biomarkers that might be able to improve the diagnosis of CRC ( 28 , 29 ). Studies by other authors suggest that, although elevated to a significant proportion in preclinical CRC, CEA alone is not sufficient as a screening tool.…”
Section: Discussionmentioning
confidence: 99%